Debt and Household Consumption Responses - Andreas Fagereng; Elin Halvorsen (Norges Bank, 2016)
Norwegian households' levels of housing wealth have since the banking crisis of the 90s become an ever more dominant part of households' portfolios. Low interest rates and easy access to mortgages have contributed to both increasing house prices and the corresponding increase in household debt. A potential concern for policy makers is how these high debt levels will affect household consumption were the economy to experience a sudden shock, in form of higher unemployment, rising interest rates, falling house prices or a combination of the three. This memo provides an overview of the theoretical implications and the empirical literature on the effects of such shocks on consumption, with an emphasis on heterogeneous responses. We use Norwegian register data on income and wealth to impute measures of consumption for the population and explore differences in consumption rates to gauge the potential impact of such shocks in Norway. We study the role of debt for consumption and find support for the hypothesis that consumption expenditure growth is lower among households with high debt. Much of the leveling off in consumption growth after the crisis reflects a regular response by highly indebted households. Still, a somewhat stronger relationship after the crisis shows that precautionary savings may have played a role.
hdl:11250/2506549
Keywords: 330